Utilização de embriões liofilizados e flocos de Artemia na diversificação nutricional de pós-larvas do camarão marinho Litopenaes vannamei (Boone, 1931) - Cavalcante, Pedro Hercílio de Oliveira (2006)
The objective of the current study was to evaluate the zootechnical performance (survival and growth) of Litopenaeus vannamei post-Iarvae fed an artificial shrimp diet supplemented with Artemia flakes or freeze-dried Artemia embryos. For that purpose, 20 culturing units were individually stocked with 50 shrimp post-Iarvae (average dry weight of 0,3 ± 0,03 mg) at a stocking density of 20 post-larvae per liter, and fed the experimental diets to satiation during 20 days. The experimental design consisted of four diets (T1, T2, T3 and T4) with five repetitions each. For treatments T1, T2 and T3, dietary supplements of 5mg of Artemia flakes (T1), freeze-dried Artemia embryos (T2), and of the commercial shrimp diet (T3) were offered 2 hours after the shrimp were initially fed the commercial shrimp diet. For treatment T4 (control), no additive was offered 2 hours after the initial feeding. Shrimp survival, absolut (GPA) and relative increase in weight (GPR), and specific growth rate (TCR) were used as evaluation criteria. After the experimental period, no significant statistical differences (p>0,05) in survival were observed. Regarding growth, the dietary treatment which used freeze-dried Artemia embryos as an additive (T2) presented the best results for GPA (6,7 ± 0,7 mg). There were no statistical differences within treatments T1, T3 and T4 (p>0,05). AIso, post-larvae fed freeze-dried embryos (T2) showed a relative increase in weight (2241,4%) which differed significantly (p<0,05) from T4(1911,7%) but not from T1 (1801,6%) or T3 (1946,7%). In conclusion, the results of the current study indicate that an artificial shrimp diet supplemented with freeze-dried Artemia embryos fulfils the nutritional requirements of post-larvae L. vannamei and promotes a better growth than diets not supplemented with Artemia flakes